2012
DOI: 10.1002/alr.21044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of steroid‐releasing sinus implants on postoperative medical and surgical interventions: an efficacy meta‐analysis

Abstract: Early postoperative healing is a predictor of longer-term success after sinus surgery. Evaluation of postoperative outcomes by a blinded independent panel demonstrates that steroid-releasing implants that provide a sustained release of corticosteroid improve surgical outcomes by reducing frank polyp formation, sinus adhesions, and middle turbinate lateralization. Steroid-releasing implants reduce the need for surgical intervention, and the need for oral steroid treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
1
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 9 publications
2
94
1
4
Order By: Relevance
“…1307,1317,1318 A meta-analysis combined the results from the 2 RCTs to demonstrate statistically significant reductions in the need for postoperative intervention, oral corticosteroid usage, polyposis, and adhesions. 1319 An economic evaluation also demonstrated that Propel TM is cost-effective in decreasing postoperative intervention. 1320 Concerns raised regarding the data to date have included the lack of a nonstented arm in these studies, which might show that the stenting material without the corticosteroid is proinflammatory.…”
Section: Xd6 Surgical Principles/techniques: Drug Eluting Packingmentioning
confidence: 99%
“…1307,1317,1318 A meta-analysis combined the results from the 2 RCTs to demonstrate statistically significant reductions in the need for postoperative intervention, oral corticosteroid usage, polyposis, and adhesions. 1319 An economic evaluation also demonstrated that Propel TM is cost-effective in decreasing postoperative intervention. 1320 Concerns raised regarding the data to date have included the lack of a nonstented arm in these studies, which might show that the stenting material without the corticosteroid is proinflammatory.…”
Section: Xd6 Surgical Principles/techniques: Drug Eluting Packingmentioning
confidence: 99%
“…Three prospective, randomized, controlled trials and one meta-analysis have demonstrated the effectiveness of steroid-eluting stents when placed in the ethmoid sinus. [6][7][8][9] Smaller implants could prove useful in maintaining frontal recess patency; however, this has not been extensively studied. Fig.…”
Section: Future Developmentsmentioning
confidence: 99%
“…This implant is bioabsorbable and lasts approximately 30 days if left in place. A recent meta-analysis by Han et al pooled data from two previous studies [ 39 ]. A total of 143 patients at 11 centers were evaluated.…”
Section: Steroid-eluting Implantsmentioning
confidence: 99%